Acoustoelastic Behaviour of Double-Layer Plates Accounting Internal Damping of Layer Materials. (2015) - Paimushin, V.N.
Abstract: In this paper, the coupled problem of planar acoustic wave propagation through the double-layer composite plate containing the second layer from damping material with high logarithmic decrement is examined. Aerohydrodynamic interaction between plate and external acoustic environment is defined by three-dimensional wave equations, whilst mechanical behaviour of double-layered plate is examined with model based on classical Kirchhoff-Love's hypothesis. Exact analytical solutions are given for plates with simply supported edges. On the basis of given solutions, parameters for second layer, which lead substantially damping of plate vibrations are found in the case of acoustic loading at resonant modes.